Pengaruh E-WOM, Kualitas Produk dan Persepsi Harga terhadap Keputusan Pembelian Skintific: (Studi pada Konsumen Skintific Mahasiswa Universitas Budi Luhur Angkatan 2021 di Jakarta) - Kania Vira Yunita; Ravindra Safitra Hidayat (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
Currently, the beauty trend has made many skincare business emerge, one of which skincare brand is Skintific, which managed to occupy the top position in skincare sales in 2024. This study aims to determine the effect of E-WOM, Product Quality and Price Perception on purchasing decisions. The population in this study were Skintific consumers, Budi Luhur University student class of 2021 in Jakarta. In this study using a survey methodin the form of a questionnaire consisting of 94 respondents, using non probability sampling technique with purposive sampling method. The results of this study indicate that E-WOM has a significant effect on purchasing decisions, Product Quality affects purchasing decisions, and Price Perception affects purchasing decisions.